Penguatan Literasi Sanitasi Kandang sebagai Upaya Pengembangan Peternakan Sapi (Bos sondaicus) Berkelanjutan di Kabupaten Lombok Utara - Syuhriatin Syuhriatin; Slamet Mardiyanto Rahayu (BEST Journal (Biology Education, Sains and Technology), 2026)
This community service activity aimed to enhance the knowledge and skills of livestock farmers regarding pen sanitation, thereby supporting the sustainable development of cattle (*Bos sondaicus*) farming within the Bina Karya Livestock Group in Sambik Elen Village, Bayan District, North Lombok Regency. The methods employed included educational sessions, interactive discussions, demonstrations, and hands-on practice in pen cleaning and livestock waste management. A participatory approach was adopted, ensuring active farmer involvement at every stage of the learning process. The results demonstrated an increase in the farmers' understanding and awareness regarding the importance of pen sanitation for maintaining livestock health, boosting productivity, and creating a cleaner, healthier farming environment. Through hands-on practice, participants learned to apply proper pen cleaning techniques and grasped the significance of environmentally friendly waste management. Overall, the activity successfully strengthened knowledge of pen sanitation and fostered a commitment among farmers to implement sanitation practices routinely as part of productive and sustainable cattle farming management.